Legal Regulations Regarding the Protection of Indigenous Peoples' Rights in Natural Resource Management - Hengki Maryono; Tri Susilowati; Mohamad Tohari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Indigenous peoples possess a strong cultural, social, and spiritual relationship with the natural resources they have traditionally managed for generations. Their customary laws and local knowledge systems play a crucial role in maintaining environmental sustainability and preserving biodiversity. However, in practice, the exploitation of natural resources by the state, private corporations, and other external actors often leads to the marginalization of indigenous peoples and the erosion of their traditional rights. Consequently, legal protection for indigenous communities in natural resource management has become an important issue in achieving a balance between economic development, environmental conservation, and human rights protection. This study aims to analyze the legal framework governing the protection of indigenous peoples’ rights in Indonesia and evaluate its conformity with international legal standards. The research employs a normative juridical method using statutory and conceptual approaches. The data are derived from legislation, international legal instruments, and relevant academic literature. The study examines various national legal instruments, including the 1945 Constitution, the Basic Agrarian Law, the Forestry Law, and the Environmental Protection and Management Law. Furthermore, it compares these regulations with international standards such as the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) and ILO Convention No. 169. The findings are expected to support the development of more equitable, inclusive, and sustainable natural resource governance in Indonesia.